Coping Strategies and Considering the Possibility of Death in Those Bereaved by Sudden and Violent Deaths: Grief Severity, Depression, and Posttraumatic Growth - Fisher, Joscelyn E.; Zhou, Jing; Zuleta, Rafael F.; Fullerton, Carol S.; Ursano, Robert J.; Cozza, Stephen J. (Frontiers in Psychiatry, 2020)
Background: Bereavement by sudden and violent deaths can lead to increased grief severity, depression and reduced posttraumatic growth compared to those bereaved by natural causes. These outcomes can be affected by coping strategies and whether a survivor had been “prepared” for the death. The present study examined the effect of coping and considering the possibility of death on grief severity, depression and posttraumatic growth in those bereaved by sudden deaths. Methods: Participants bereaved by suicide, accident or combat deaths completed an online survey about demographics (including the cause of death), coping, grief severity, depression, and posttraumatic growth. A factor analysis of the coping measure yielded factors representing three coping strategies: avoidant coping, supportive coping and active coping. These three strategies, the causes of death and considering the possibility of death were used as predictors of either grief severity, depression or posttraumatic growth in multivariate linear regression models. Results: Each coping strategy and cause of death was differentially associated with grief severity, depression and posttraumatic growth. Specifically, supportive coping and active coping were each only associated with higher posttraumatic growth. In contrast, avoidant coping was associated with all outcomes (higher grief severity and depression and lower posttraumatic growth). In addition, accidents and suicides (compared to combat deaths) had independent effects on grief severity and posttraumatic growth. Considering the possibility of death interacted with avoidant coping and also with supportive coping to predict grief severity in combat-loss survivors. Discussion: Findings highlight the differential contributions of coping strategies and their complex relationships with cause of death in contributing to grief severity, depression and posttraumatic growth. Avoidant coping contributed to negative outcomes and inhibited posttraumatic growth, suggesting its importance as a target for therapeutic intervention. Although supportive and active coping facilitated posttraumatic growth, they had less of a role in mitigating grief severity or depression in this study. Although considering the possibility of death appeared to mitigate negative outcomes among survivors of combat death, avoidance of that possibility is likely protective for the majority of family members whose loved ones return home safely.